Internalization and Transportation of Endothelial Cell Surface KCa2.3 and KCa3.1 in Normal Pregnancy and Preeclampsia. (23rd November 2019) - Choi, Shinkyu; Kim, Ji Aee; Oh, Seikwan; Park, Mi Hye; Cho, Geum Joon; Suh, Suk Hyo
Abstract : Altered redox state modulates the expression levels of endothelial KCa 2.3 and KCa 3.1 (KCa s) in normal pregnancy (NP) and preeclampsia (PE), thereby regulating vascular contractility. The mechanisms underlying KCa s endocytosis and transportation remain unknown. We investigated the regulation of KCa s expression in plasma membrane (PM) during NP and PE. Cultured human uterine artery endothelial cells were incubated in serum from normal nonpregnant women and women with NP or PE, or in oxidized LDL-, or lysophosphatidylcholine- (LPC-) containing a medium for 24 hours. NP serum elevated PM levels of KCa s and reduced caveolin-1 and clathrin levels. PE serum, oxidized LDL, or LPC reduced PM levels of KCa s and elevated caveolin-1, clathrin, Rab5c, and early endosome antigen-1 (EEA1) levels. Reduced KCa s levels by PE serum or LPC were reversed by inhibition of caveolin-1, clathrin, or EEA1. Catalase and glutathione peroxidase 1 (GPX1) knockdown elevated PM-localized KCa s levels and reduced caveolin-1 and clathrin levels. Elevated KCa 2.3 levels upon catalase and GPX1 knockdown were reversed by PEG-catalase treatment. An H2 O2 donor reduced clathrin and Rab5c. In contrast, elevated clathrin, caveolin-1, or colocalization of caveolin-1 with KCa 3.1 by PE serum or LPC was reversed by NADPH oxidase inhibitors or antioxidants. A superoxide donor xanthine+xanthine oxidase elevated caveolin-1 or Rab5c levels. We concluded that KCa s are endocytosed in a caveola- or a clathrin-dependent manner and transported in a Rab5c- and EEA1-dependent manner during pregnancy. The endocytosis and transportation processes may slow down via H2 O2 -mediated pathways in NP and may be accelerated via superoxide-mediated pathways in PE.